Cytotoxic T-Cell Trafficking Chemokine Profiles Correlate With Defined Mucosal Microbial Communities in Colorectal Cancer - Zhang, Jiali; Tao, Ji; Gao, Ruo-Nan; Wei, Zhi-Yuan; He, Yu-Shan; Ren, Chun-Yan; Li, Qi-Chun; Liu, Yan-Shan; Wang, Ke-Wei; Yang, Gong; Qian, Chengjia; Chen, Jian-Huan (Frontiers in Immunology, 2021)
The involvement of gut microbiota in T cell trafficking into tumor tissue of colorectal cancer (CRC) remains to be further elucidated. The current study aimed to evaluate expression of major cytotoxic T cell trafficking chemokines (CTTCs), and chemokine-associated microbiota profiles in both tumor and adjacent normal tissues during CRC progression. We analyzed the expression of chemokine C-X-C motif ligand 9, 10, 11 (CXCL9, CXCL10, CXCL11), and C-C motif ligand 5 (CCL5), characterized gut mucosa-associated microbiota (MAM), and investigated their correlations in CRC patients. Our results showed that the expressions of CXCL9, CXCL10 and CXCL11 were significantly higher in tumor than in adjacent normal tissues in 136 CRC patients. Notably, high expression of CXCL9 in tumor tissues was associated with enhanced CD8+ T cell infiltration and improved survival. Moreover, the MAM in tumor tissues showed reduction of microbial diversity and increase of oral bacteria. Microbial network analysis identified differences in microbial composition and structure between tumor and adjacent normal tissues. In addition, stronger associations between oral bacteria and other gut microbes were observed. Furthermore, the correlations analysis between the defined MAM and individual CTTCs showed that the CTTCs’ correlated OTUs in tumor and adjacent normal tissues rarely overlap with each other. Notably, all the enriched OTUs were positively correlated with the CTTCs in either tumor or adjacent normal tissues. Our findings demonstrated stronger interactions between oral bacteria and gut microbes, and a shifted correlation pattern between MAM and major CTTCs in tumor tissues, underlining possible mechanisms of gut microbiota-host interaction in CRC.